Three-dimensional evaluation of the alar cinch suture after Le Fort I osteotomy. Issue 10 (October 2016) - van Loon, B.; Verhamme, L.; Xi, T.; de Koning, M.J.J.; Bergé, S.J.; Maal, T.J.J.
Abstract: Orthognathic surgery has an influence on the overlying soft tissues of the translated bony maxillomandibular complex. Improvements in both function and facial appearance are the goals of surgery. However, unwanted changes to the soft tissues, especially in the nose region, frequently occur. The most common secondary change in the nasolabial region is widening of the alar base. Various surgical techniques have been developed to minimize this effect. The purpose of this study was to evaluate the changes in the nasal region due to orthognathic surgery, especially the alar width and nasal volume, using combined cone beam computed tomography (CBCT) and three-dimensional (3D) stereophotogrammetry datasets. Twenty-six patients who underwent a Le Fort I advancement osteotomy between 2006 and 2013 were included. From 2006 to 2010, no alar base cinch sutures were performed. From 2010 onwards, alar base cinch sutures were used. Preoperative and postoperative documentation consisted of 3D stereophotogrammetry and CBCT scans. 3D measurements were performed on the combined datasets, and the alar base width and nose volume were analyzed. No difference in alar base width or nose volume was observed between patients who had undergone an alar cinch and those who had not. Postoperatively the nose widened and the volume increased in both groups.